Exploring Diagnostic Assesment as an Instrumen for Learning Improvement - Mukhammad Bakhruddin; Sugito Muzaqi; Kusaeri Kusaeri; Lailah Isrofatun Nahdiah; Mirwan Ahmad Taufiq (Universitas Muhammadiyah Malang, 2023)
This study aims to diagnose assessment as one of the learning improvement instruments. Assessment or assessment is a very urgent part of learning activities. From the diagnostic results, it is stated that the assessment has a positive impact on learning. One form of assessment that is often used is formative assessment. This research was conducted with a quantitative approach. Data collection techniques were carried out by questionnaires, interviews, and documentation. Questionnaires were distributed via google form using a liket scale. The research was conducted at madrasas within the scope of the East Java region. The number of respondents consisted of ninety students. The results showed that diagnostic assessment as a learning improvement instrument that was integrated with PAI was very effective in increasing the motivation of madrasa students. Diagnostic assessment also has a positive effect on learning awareness. Diagnostic assessment gives a positive response to learning tools or learning media. Diagnostic assessment has a positive influence on the innovation of madrasa students.